UJI DAYA HAMBAT EKSTRAK MENIRAN (Phyllanthus niruri L.) TERHADAP PERTUMBUHAN Candida albicans. - Pratiwi Yusni, Melsi; Indriati, Gustina; Irdawati, Irdawati (STKIP PGRI Sumbar, 2014)
ABSTRAC Meniran ( Phyllanthus. niruri L. ) or known to the sidukuang anak a potent plant can treat a variety of diseases . Meniran ( P. niruri L.) which contains antimicrobial flavonoid, saponin and tanin that can inhibit the growth of C. albicans . Has done research on Power Test Inhibitory Meniran Extract ( Phyllanthus niruri ) on growth of C. albicans . This study used a Completely Randomized Design ( CRD ) with 7 treatments and 3 replications , treatment begins albothyl 2 % of control ( A ), Concentration 5 % ( B ), concentration of 10 % ( C ), concentration of 30 % ( D ) , Concentration 40 % ( E ) , concentration of 50 % ( F ). Data processed by Analysis Of Variance ( ANNOVA ). This study aims to determine the inhibitory meniran extract ( P. niruri L.) on the growth of C. albicans , and to determine the most effective concentration of meniran ( P. niruri L.) on the growth of C. albicans has been done in the laboratory of the UNP . From the research that has been done , it can be concluded that the extract meniran ( P. niruri L.) ranging from 5 % concentration was able to inhibit the growth of C. albicans . The most effective concentration present in a concentration of 20 % .